Isoprostane and isofuran lipid mediators accumulate in stored red blood cells and influence platelet function in vitro. Issue 6 (5th November 2013) - Spinelli, Sherry L.; Lannan, Katie L.; Casey, Ann E.; Croasdell, Amanda; Curran, Timothy M.; Henrichs, Kelly F.; Pollock, Stephen J.; Milne, Ginger A.; Refaai, Majed A.; Francis, Charles W.; Phipps, Richard P.; Blumberg, Neil
<x xml:space="preserve">Abstract</x> Background Stored red blood cells (RBCs) release hemoglobin (Hb) that leads to oxidative damage, which may contribute to thrombosis in susceptible transfusion recipients. Oxidative stress stimulates the generation of a new class of lipid mediators called F2‐isoprostanes (F2‐IsoPs) and isofurans (IsoFs) that influence cellular behavior. This study investigated RBC‐derived F2‐IsoPs and IsoFs during storage and their influence on human platelets (PLTs). Study Design and Methods F2‐IsoP and IsoF levels in RBC supernatants were measured by mass spectrometry during storage and after washing. The effects of stored supernatants, cell‐free Hb, or a key F2‐IsoP, 8‐iso‐prostaglandin F2α (PGF2α), on PLT function were examined in vitro. Results F2‐IsoPs, IsoFs, and Hb accumulated in stored RBC supernatants. Prestorage leukoreduction reduced supernatant F2‐IsoPs and IsoFs levels, which increased again over storage time. Stored RBC supernatants and 8‐iso‐PGF2α induced PLT activation marker CD62P (P‐selectin) expression and prothrombotic thromboxane A2 release. Cell‐free Hb did not alter PLT mediator release, but did inhibit PLT spreading. Poststorage RBC washing reduced F2‐IsoP and IsoF levels up to 24 hours. Conclusions F2‐IsoPs and IsoFs are produced by stored RBCs and induce adverse effects on PLT function in vitro, supporting a potential novel role for bioactive lipids in adverse transfusion outcomes. F2‐IsoP and IsoF levels could be useful biomarkers for determining the suitability of blood components for transfusion. A novel finding is that cell‐free Hb inhibits PLT spreading and could adversely influence wound healing. Poststorage RBC washing minimizes harmful lipid mediators, and its use could potentially reduce transfusion complications.